The new challenges of the right to identity in Peru: from hetero assignment to self-determination - Díaz Díaz, Maria-Pía Guadalupe (2020)
This study analyzes the current situation of the constitutional model for the recognition of gender identity in force in Peru, a hetero-assigned model that has been replicated in specific cases before the ordinary courts and that is read separately from the recent Advisory Opinion OC-24/17 of the Inter-American Court of Human Rights. There has been an important jurisprudential development  in constitutional matters that has reached the recognition of a right to gender identity; however, it is necessary to delve into the problem that now focuses on the form and scope of this recognition, where self-determination is presented as a pending and necessary challenge from the perspective of Human Rights.